2018
DOI: 10.1016/j.matlet.2017.11.115
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and properties of l -arginine-doped PCL electrospun composite scaffolds

Abstract: The article describes fabrication and properties of composite fibrous scaffolds obtained by electrospinning of the solution of poly(ε-caprolactone) and arginine in common solvent. The influence of arginine content on structure, mechanical, surface and biological properties of the scaffolds was investigated. It was found that with an increase of arginine concentration diameter of the scaffold fibers was reduced, which was accompanied by an increase of scaffold strength and Young modulus. It was demonstrated tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 14 publications
(14 reference statements)
0
10
1
Order By: Relevance
“…Other researchers have shown that, when using arginine injection into PCL solution during the preparation of scaffolds using the electrospinning method, arginine affects the diameter of the formed fibrils [16]. The conditions of our modification did not reveal significant changes in the surface topology of the PCL films before and after treatment with arginine solution.…”
Section: Resultsmentioning
confidence: 57%
See 2 more Smart Citations
“…Other researchers have shown that, when using arginine injection into PCL solution during the preparation of scaffolds using the electrospinning method, arginine affects the diameter of the formed fibrils [16]. The conditions of our modification did not reveal significant changes in the surface topology of the PCL films before and after treatment with arginine solution.…”
Section: Resultsmentioning
confidence: 57%
“…Our results demonstrate that modifying the PCL films with arginine significantly increased the number of adhered and proliferating cells (Figure 4). It should be noted that, after MSC cultivation for 1 day on films modified with a 0.5 M arginine solution at 40 °C, the number of adherent cells was Other researchers have shown that, when using arginine injection into PCL solution during the preparation of scaffolds using the electrospinning method, arginine affects the diameter of the formed fibrils [16]. The conditions of our modification did not reveal significant changes in the surface topology of the PCL films before and after treatment with arginine solution.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With PVP increase from 0 to 50 wt%, the Young modulus increased for more than five times, while the elongation decreased by more than 80%. Materials with PCL/PVP ratio of 50/50 demonstrated Young modulus of 105.4 ± 8.4 MPa which is significantly higher than for the majority of the reported PCL‐based (e.g., 34 ± 3 MPa for L‐arginine‐doped scaffolds 29 ; 19.5 MPa for nano‐hydroxyapatite‐doped scaffolds 30 ) and PCL/PVP (e.g., 39.270 ± 1.871 MPa by Kim et al 24 ) electrospun scaffolds.…”
Section: Resultsmentioning
confidence: 67%
“…Despite all the advantages and the fact that several PCL-based medical devices have been already approved by FDA to be used in human 16 , the hydrophobicity of PCL and a lack of functional groups hinder the material interaction with surrounding cells and tissues 17 . Several approaches have been applied to improve electrospun PCL-based scaffolds properties including surface modification 18,19 and composite production [20][21][22][23] . Previously we have reported that polymer biodegradable scaffolds can be modified by reactive magnetron plasma that occurres under a working gas atmosphere during the sputtering of a solid target [24][25][26] .…”
Section: Introductionmentioning
confidence: 99%